Komunikasi SBAR Perawat Dan Dokter Dalam Kolaborasi Interprofesional Di Rumah Sakit X - Putri Natalia Millu (Lembaga Pengembangan Kinerja Dosen, 2023)
Interprofessional Collaboration (IPC) is professional collaboration with different educational backgrounds and collaborates to improve service quality. The purpose of this study was to explore SBAR communication carried out by nurses and doctors in IPC at the Hospital X. The research method is qualitative. The research participants were 10 health workers (5 nurses and 5 doctors). Data analysis was carried out by processing and preparing data, reading data, coding, coding interpretation, presenting themes, and interpreting data. The results showed that there were three themes produced: 1) A thorough assessment by nurses and doctors; 2) Collaboration between nurses and doctors to patients; 3) Barriers communication between nurses and doctors. The form of communication that is applied between doctors and nurses in the emergency room at the hospital x is SBAR communication that has been implemented well. The main barriers to SBAR communication are the shortage of staff and the increase in the number of patients. And the obstacle from the doctor's side is the new nurse personnel who do not really understand their duties. The conclusion of this study is that the application of SBAR communication in the Interprofessional Collaboration (IPC) relationship between nurses and emergency room doctors at the hospital x is good, but there are still barriers to SBAR communication when there is an increase in the number of patients due to lack of staff in the hospital.